Generation Y expectations for the location of web objects - Aslina Baharum; Azizah Jaafar (Advanced Institute of Convergence IT, 2014)
This study examined the expectations among Generation Y (Gen Y) individuals (age 18-31) regarding the location of specific objects on a webpage. The Web objects were obtain from previous studies with additional common identified: logo, site title, login, search engine, internal links, external links, language selection, content, calendar and advertisements. The results found that Gen Y expectations regarding the location of these Web objects were not significantly different from the expectations among other age groups except in relation to two objects, namely, external links and advertisements. This study may help the web developers and the managers to improve the usability of web user interface especially targeting this Gen Y group as target market.